Websites Use as Learning Resources in Developing Intercultural Communicative Competence in English Language Teaching Classroom - Marwa Marwa; Herdi Herdi; M. Fadhly Farhy Abbas (ELT-Lectura, 2022)
This classroom action research (CAR) aims at developing students’ intercultural competence (ICC) and exploring English language learning models integrated to ICC on the basis of websites use as the learning resource. This research was conducted in Intensive Course online class involving 24 students of English study program in Universitas Lancang Kuning. This CAR was conducted in one cycle consisting of 6 meetings and 2 evaluations. The data was collected from (1) observation fieldnotes, (2) observation checklist, (3) collecting documents (students’ comments and accessed websites, and (4) the scores taken from the 5 groups’ discussion. This research reveals the students’ ICC dimensions development exhibited in their class discussions with the increasing percentage from 46.15% to 92.30%). Some language learning models integrated to ICC on the basis of websites use were identified: (1) Accessing websites related to ICC learning topics, and (2) accessing websites that provide authentic materials (texts, pictures, audio-videos, and (3) motivating students to communicate and collaborate with others via online learning media. This CAR concludes that “students’ ICC could be developed through language learning on the basis of websites use which contains ICC dimensions”.